METACERCARIAE OF CLINOSTOMUM SP. (TREMATODA: CLINOSTOMIDAE) INFESTING ORNAMENTAL CICHLIDS CULTIVATED IN THE PERUVIAN AMAZONIA - Murrieta-Morey, Germán Augusto (2022)
The ornamental fish trade is one of the most important economic activities for thousands of people in the Amazon region. Among fish that are exported from Peru, Apistogramma sp., Cichlasoma amazonarum (Kullander, 1983) and Pterophyllum scalare (Schultze, 1823) are highly demanded in the ornamental fish trade activities. To date, in Peru, studies concerning to parasites that affect aquaculture activities are scarce, in that way, the present study registers for the first time in the Peruvian Amazonia the occurrence of Clinostomum sp. parasitizing three species of cichlids. Samples of Apistogramma sp., C. amazonarum and P. scalare were collected in a fish farming pond of the “Amazon Research Center for Ornamental Fishes (ARCOF) in Iquitos, Peru. Analyzed samples revealed the presence of Clinostomum sp. parasitizing the fins of the fish. As some species of cichlids are cultivated in the Peruvian Amazon for exportation as ornamental fish, the presence of this trematode could compromise the health of the fish and to cause mortalities, either, due to susceptibility to predation by piscivorous birds or due to injuries caused by the infection of parasites.